IMPROVING BIOLOGY LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF THE COURSE REVIEW HORAY (CRH) COOPERATIVE LEARNING MODEL: Peningkatan Hasil Belajar Biologi melalui Penerapan Model Pembelajaran Kooperatif Tipe Course Review Horay (CRH) - Yuliarti Ramli; Nur Zakiyah R; Fatmah Damayanti (Jurnal Bionatural, 2024)
Based on the observation in SMA Negeri 1 Parepare, it shows that the average of biology learning result of students of XI.MIA.3 grade in Senior High School 1 of Parepare is 70, it’s doesn’t reach KKM 75. In this case, the cooperative learning model with Course Review Horay (CRH) type. This research aims to improve student learning result. This research was began July until the August 2023. Results of research and discussion found that the biology learning results of students of XI.MIA.3 grade in Senior High School 1 of Parepare has increased through the implementation cooperative learning model with CRH type. This is indicated by the increase of average score in cycle I that is 66,45 increase in cycle II that is 84,6.